2020
DOI: 10.1002/lpor.201900146
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Entanglement Based on Nonlinear Metamaterials

Abstract: Metamaterials consisting of deep subwavelength artificial “atoms” have been utilized to demonstrate a series of novel phenomena such as negative refraction and epsilon‐near‐zero. In recent times, metamaterials have been developed as an up‐and‐coming platform for quantum optics. Here the generation and modulation of photonic entanglement are investigated based on the parametric down conversion processes in metamaterials with considerable optical nonlinearity. Through flexible nanostructure design, the nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Several composite modes with different combinations of l 1 , l 2 , and l 3 at z = 0 are initially simulated. The selected combinations include (l 1 , l 2 , l 3 ) = (2, 3, 5), (2,4,8), and (2,5,11), where…”
Section: Superposition Of Three Lg Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several composite modes with different combinations of l 1 , l 2 , and l 3 at z = 0 are initially simulated. The selected combinations include (l 1 , l 2 , l 3 ) = (2, 3, 5), (2,4,8), and (2,5,11), where…”
Section: Superposition Of Three Lg Beamsmentioning
confidence: 99%
“…The nontrivial behaviors of phase give rise to diverse intriguing phenomena, opening up the area of singular optics. [1] Optical vortices (known as singular light beams) have been used in many fields ranging from particle manipulation [2,3] to quantum information [4,5] due to their unique optical properties. The singularity structure of a wavefront plays an important role in the physical properties of vortex beams.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, there has been so many works concerning how to augment and control nonlinear frequency conversion, and these works provide enormous and rich knowledge for manipulation of quantum source. In fact, 5 times enhancement of SP-DC efficiency is attainable from subwavelength films made of GaP 86 , the enhancement originates from Fabry-Perot resonance inside the nonlinear films. Take it further, Y. Ming et al theoretically demonstrated that by judiciously designing metamaterials, desired quantum state could be prepared from metamaterials 87 .…”
Section: N × Nmentioning
confidence: 99%
“…From Figure 1b, it can be seen that the absolute value of χ (2) varies with the arm and base lengths L a and L b of meta-atom, and the sign of χ (2) changes when the orientation of meta-atom is inverted. 13 Based on this approach, any wavy distribution of χ (2) can be acquired through designing the nanostructures of nonlinear metasurfaces in theory. However, as the meta-atoms are discretized, the variation of χ (2) is quasi-continuous.…”
mentioning
confidence: 99%
“…For linear optical applications, various functional devices like phase-only transmissive spatial light modulator and electromagnetically induced absorber have been demonstrated based on metasurfaces with rationally designed nanostructures. Recently, as a further step, the potential of nanopatterned interfaces in the field of nonlinear optics draws considerable attention. In early studies, nonlinear interactions at such interfaces always suffer from low conversion efficiency. , The exploitation of multi-quantum-wells (MQWs) with giant second-order nonlinearity for metasurfaces substantially eases the problem, which paves the way for further development of this direction.…”
mentioning
confidence: 99%